Is inguinal hernia mesh safe? A prospective study. Issue 4 (30th November 2019) - Watson, Bridget; Roberts, Jessica; Dobbs, Bruce; Roberts, Ross
Abstract: Background: Hernia repair surgery using synthetic mesh is the standard of care in modern surgery. Complications from uro‐gynaecological mesh have been reported in the New Zealand media and there is public concern regarding the use of any mesh for any reason. This study reports long‐term outcomes in inguinal hernia surgery in a large cohort of elective operations using mesh. Methods: A prospective database of patients having inguinal hernia mesh repairs was maintained in a private two surgeon practice from 2002 to 2016. Patient demographics, method of repair, the pre‐operative and post‐operative pain scores and complications following surgery were recorded. Results: A total of 1711 hernia in 1366 patients were repaired from 2002 to 2016. One thousand and forty‐seven repairs were laparoscopic total extraperitoneal (LTEP), 333 were open. Post‐operative pain scores were significantly lower than pre‐operative scores in inguinal hernia repair by any method. Only 22% of patients described no pain pre‐operatively and this rose to 76% post‐operatively; conversely 7.9% described severe pain pre‐operatively and this reduced to 1% post‐operatively. The recurrence rate for open inguinal hernia was zero and for LTEP repair was 0.81%. Conclusion: Inguinal hernia repair using mesh does not appear to produce significant rates of chronic pain long term. Overall, the complications from open or LTEP inguinal hernia repair with mesh are low. Abstract : There is public concern regarding mesh in inguinal hernia repairs in New Zealand. This study has followed 1366 patients having open or laparoscopic total extraperitoneal repair with mesh for a year. Pain improved significantly post‐operatively.